2015
DOI: 10.3892/ol.2015.3555
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasm estrogen receptor β5 as an improved prognostic factor in thymoma and thymic carcinoma progression

Abstract: Abstract. A number of previous studies have reported that sex steroid hormones, including estrogens, are involved in the regulation of the thymic function. The aim of the present study was to investigate the expression of estrogen receptor β5 (ERβ5) in thymic tumors and the correlation between ERβ5 expression and thymoma biological characteristics. The expression levels of ERβ5 in thymic epithelial tumors was evaluated in 103 patents using immunohistochemical staining and reverse transcription-quantitative pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…Our studies in endometrial cancer tissue are in agreement with other results reporting expression of ERβ5 protein is upregulated in a number of hormone-responsive cancers compared with equivalent non-malignant tissues (Li et al . 2015).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our studies in endometrial cancer tissue are in agreement with other results reporting expression of ERβ5 protein is upregulated in a number of hormone-responsive cancers compared with equivalent non-malignant tissues (Li et al . 2015).…”
Section: Discussionsupporting
confidence: 93%
“…Over-expression of ERβ5 has also been reported in colon cancers (Wong et al . 2005), glioma (Li et al 2013), cancers of the ovary (Ciucci et al 2014) and of the thymus (Li et al 2015); however, to date, the impact of ERβ5 in endometrial cancers is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, in a study published in 2015 the expression levels of the ERβ5 variant were analyzed in a set of tissue microarrays from a cohort of patients with thymic tumors (n=103) by immunohistochemistry (98). The results revealed that ERβ5 was overexpressed and predominantly located in the cytoplasm (cERβ5) of thymic tumors.…”
Section: Subtypes: Thymoma Thymic Carcinomamentioning
confidence: 99%